“Indefinite for Dysplasia” in Barrett's Esophagus: Inflammation and DNA Content Abnormality are Significant Predictors of Early Detection of Neoplasia - Choi, Won-Tak (Clin Transl Gastroenterol, 2015)
BACKGROUND: Dysplasia arising from Barrett's esophagus precedes esophageal adenocarcinoma (EAC). Cases that are difficult to diagnose as dysplastic, especially in the setting of inflammation, may be designated “indefinite for dysplasia (IND).” Although flow cytometric analysis of DNA content has shown some promise in detecting EAC, there are few reports that have specifically evaluated the outcome of IND. AIMS AND METHODS: We analyzed a series of 96 IND patients seen at the University of Washington between 2005 and 2013 to determine the outcome of IND and to identify factors (including histologic features and DNA flow cytometric data) associated with subsequent detection of neoplasia. RESULTS: Twenty-five percent of IND cases were found to have low-grade dysplasia, high-grade dysplasia (HGD), or EAC within 1 year, with 37% and 47% detected within 2 and 3 years, respectively. The 1-, 2-, and 3-year detection rates of HGD or EAC were 10%, 13%, and 20%, respectively. Active inflammation (hazard ratio (HR)=3.4, P=0.0005) and abnormal DNA content (HR=5.7, P=0.003) were significant risk factors of neoplasia. When active inflammation and DNA flow cytometric results were considered together, the HR for the combined markers was 18.8 (P<0.0001). The sensitivity and specificity of the combined markers for predicting detection of subsequent neoplasia within 3 years were 100% and 60%, respectively, with 100% negative and 89% positive predictive values. CONCLUSIONS: Histology with the support of DNA flow cytometry can identify a subset of IND patients who may have a higher risk for subsequent detection of neoplasia.